Etiology and Characteristics of Amputations in Saudi Arabia: A Retrospective Study from a Tertiary Rehabilitation Center (Global Journal of Medical Research, 2023)
Background Limb amputation significantly impacts the patient s physical emotional and social life Multiple etiological factors may lead to limb amputation Unfortunately there is limited data about amputation in Saudi Arabia Since Sultan Bin Abdulaziz Humanitarian City SBAHC is a tertiary center receiving such patients we collected data from ten years to look at the etiology characteristics and clinical impact of amputations in the Kingdom Objective This study aimed at identifying the etiology characteristics and risk factors for amputation cases in Saudi Arabia Methods Differences in amputee patients data at SBAHC collected over ten years were analyzed using appropriate statistical tests In addition we collected Functional independent measurement FIM scores for 618 SBAHC rehabilitation program participants